Spring viraemia of carp virus modulates the time-dependent unfolded protein response to facilitate viral replication - Romero, Alejandro; Figueras, Antonio; Novoa, Beatriz (Frontiers in Immunology, 2025)
IntroductionThe spring viraemia of carp virus (SVCV) poses a significant threat to global aquaculture, yet effective antiviral drugs and vaccines remain unavailable. Understanding the interplay between host-pathogen interactions and SVCV replication is crucial for devising preventive strategies.MethodsZF4 cells were exposed to UV-inactivated SVCV or live SVCV at different multiplicities of infection, and the modulation of the unfolded protein response (UPR) was assayed by qPCR at different times. Moreover, ZF4 cells were treated with several UPR modulators to investigate their effect on viral replication. The UPR was also modulated in vivo in zebrafish larvae, and its impact on the survival against SVCV infection was evaluated.Results and conclusionsThis study reveals how SVCV exploits the host’s UPR to facilitate its replication. SVCV targets the immunoglobulin heavy chain-binding protein (BiP) and the activating transcription factor 4 (ATF4) during early infection to enhance viral RNA synthesis and translation. At later stages, activation of the BiP, the PKR-like ER kinase (PERK), and the inositol-requiring enzyme 1 alpha (IRE1α) pathways supports the release of viral progeny and induces cellular processes, including immune responses and apoptotic cell death. Furthermore, the data demonstrate that modulating UPR pathways, particularly ATF6 and PERK, significantly affect viral replication, providing a novel avenue for antiviral drug development. Preliminary in vivo studies suggest the feasibility of chemically modulating the UPR to combat SVCV, though optimizing administration conditions to maximize efficacy while minimizing side effects warrants further investigation. These findings offer critical insights into the molecular mechanisms underlying SVCV pathogenesis and highlight promising targets for therapeutic intervention.